Association of IRF6 and rs22355371 polymorphism mutation with risk of non-syndromic orofacial cleft - Al Hafiz; Benni Raymond; Hirowati Ali; Husna Yetti; Dolly Irfandy; Fauzia Latifah Supriyadi (PERHATI-KL, 2026)
Background: Non-syndromic orofacial cleft (NSOFC) is a congenital abnormality characterized by incomplete division of the oral and nasal cavities, with no other abnormalities present. NSOFC is the result of disruptions in the normal biomolecular processes of craniofacial development. Many genes have been linked to NSOFC, one of them is IRF6 gene. Purpose: To investigate the association of IRF6 gene and incident of rs22355371 mutation, with the risk of developing NSOFC. Method: A cross-sectional comparative study, conducted in DR M Djamil General Hospital Padang Indonesia from September 2024 to November 2024 involving 13 lip or palate tissues from patient with NSOFC, and 13 maxillary crest from controls. Expression of IRF6 was examined with real time polymerase chain reaction (RT PCR) and the segment of rs22355371 was examined with Sanger sequencing. Result: IRF6 gene expression was shown to have a median value of 129.3 in NSOFC patients, and 252.5 in controls. This indicated that IRF6 gene expressions were lower in NSOFC patients. The Mann Whitney test was performed had it can be concluded that there is no statistically significant relation between IRF6 gene expression between NSOFC patients and controls with a p value = 0.174 (p > 0.05). Conclusion: Compared to controls, NSOFC patients had decreased levels of IRF6 gene expression and we found rs22355371 polymorphism either in NSOFC patient or controls.